PENGARUH ETOS KERJA TERHADAP KINERJA GURU DENGAN GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA SEBAGAI VARIABEL MODERASI PADA SEKOLAH DASAR NEGERI UPTD PENDIDIKAN KECAMATAN BANYUMANIK KOTA SEMARANG - sugimin - (JURNAL EKONOMI MANAJEMEN AKUNTANSI, 2012)
The aim from this research analyzes work ethic influence towards teacher job performance with leadership style and work environment as moderating variable. Population in this research entire teachers at SDN UPTD Pendidikan Kecamatan  Banyumanik Semarang that numbers 652 person. In this research sample that be taken as much as 130 teachers (20 % from population). Analyzer that used in this research is moderated regression analysis.Hypothesis testing  known that positive influential work ethic towards teacher job performance,  leadership style and work environment moderated positive influence work ethic towards teacher job performance. Keyword: Work ethic, leadership style, work environment, teacher job performance